2018
DOI: 10.1038/s41398-018-0146-2
|View full text |Cite
|
Sign up to set email alerts
|

Reduced levels of miRNAs 449 and 34 in sperm of mice and men exposed to early life stress

Abstract: Exposure of male mice to early life stress alters the levels of specific sperm miRNAs that promote stress-associated behaviors in their offspring. To begin to evaluate whether similar phenomena occur in men, we searched for sperm miRNA changes that occur in both mice and men exposed to early life stressors that have long-lasting effects. For men, we used the Adverse Childhood Experience (ACE) questionnaire. It reveals the degree of abusive and/or dysfunctional family experiences when young, which increases ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
132
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(148 citation statements)
references
References 41 publications
9
132
0
1
Order By: Relevance
“…Finally, various paternal preconception environmental exposures directly affect the noncoding RNA milieu in sperm (Chen et al., ; Fullston et al., ; Gapp et al., ; Rodgers et al., ; Sharma et al., ; Short et al., ). In humans, alterations in sperm small noncoding RNAs have been associated with obesity (Donkin et al., ), early life stress (Dickson et al., ), and smoking history (Marczylo et al., ). Aside from sperm RNA abundance, there is increasing interest in posttranscriptional RNA modifications (i.e., the epitranscriptome) as some of these modifications on sperm RNA were found to be sensitive to paternal diet (Chen et al., ) and deletion of the RNA methyltransferase gene DNMT2 is necessary for an established model of RNA‐mediated inheritance of glucose intolerance from paternal high‐fat diet (Zhang et al., ).…”
Section: Effects Of Environmental Insults On Epigenetic Mechanisms Inmentioning
confidence: 99%
“…Finally, various paternal preconception environmental exposures directly affect the noncoding RNA milieu in sperm (Chen et al., ; Fullston et al., ; Gapp et al., ; Rodgers et al., ; Sharma et al., ; Short et al., ). In humans, alterations in sperm small noncoding RNAs have been associated with obesity (Donkin et al., ), early life stress (Dickson et al., ), and smoking history (Marczylo et al., ). Aside from sperm RNA abundance, there is increasing interest in posttranscriptional RNA modifications (i.e., the epitranscriptome) as some of these modifications on sperm RNA were found to be sensitive to paternal diet (Chen et al., ) and deletion of the RNA methyltransferase gene DNMT2 is necessary for an established model of RNA‐mediated inheritance of glucose intolerance from paternal high‐fat diet (Zhang et al., ).…”
Section: Effects Of Environmental Insults On Epigenetic Mechanisms Inmentioning
confidence: 99%
“…The offspring of veterans of Serbian-Bosnian war with PTSD also have neurodevelopmental delays and emotional deficits [30] while daughters of Finnish women evacuated during the Second World War have increased risk of psychiatric hospitalization [31]. A very recent study examined the sperm of men with adverse childhood experiences and showed alterations in some miR-NAs that are similar to that observed in mice exposed to stress and their offspring [32 ]. These results provide encouraging evidence that like in experimental animals, the germline may be implicated in epigenetic inheritance in humans.…”
Section: Inter-and Transgenerational Epigenetic Inheritance Of Negatimentioning
confidence: 92%
“…Importantly, the same study demonstrated a similar miRNA signature in the sperm of men who had experienced an adverse childhood. 104 Rodgers et al elegantly showed that chronic stress in early life or in adult males decreased HPA responsiveness to stress in offspring, as well as, inducing widespread changes in gene expression in the PVN and bed nucleus of the stria terminalis (BNST). The group went on to show that these genes sets were enriched to be targeted by miRNA.…”
Section: Mechanis Ms Of Paternal Prog R Ammingmentioning
confidence: 99%